First Description of Histopathological Lesions associated with a Fatal Infection of Moose (Alces Alces) with the Liver Fluke Parafasciolopsis Fasciolaemorpha Ejsmont, 1932 - Filip-Hutsch, Katarzyna (J Vet Res, 2019)
INTRODUCTION: Parafasciolopsis fasciolaemorpha is a liver fluke typically parasitising moose in Central and Eastern Europe. The aim of our studies was to describe a case of fatal moose parafasciolopsosis, with special emphasis on the histopathological changes caused in the liver tissue by around 10,000 flukes. MATERIAL AND METHODS: A male moose, found dead in Polesie National Park, eastern Poland, was subjected to parasitological necropsy. Macroscopic and histopathological examination of the liver was performed. RESULTS: Over 10,000 flukes identified as P. fasciolaemorpha were isolated from the liver parenchyma. Histopathological examination of the liver revealed the presence of multiple cavities, which were filled with flukes and cellular detritus and encysted with a layered capsule of connective tissue. Extensive liver fibrosis with signs of incomplete septal cirrhosis was also observed. CONCLUSION: Parafasciolopsosis with accompanying diarrhoea was the most probable reason for the moose’s death. However, it is possible that most moose are able to survive extremely intensive P. fasciolaemorpha infection by formation of extensive fibrosis, which isolates flukes from the liver parenchyma and therefore retards the failure of the organ. To the best of our knowledge, this is the first histopathological description of changes in the liver of a moose infected with P. fasciolaemorpha.